Perancangan Destination Branding Desa Wisata Kerta di Kecamatan Payangan Kabupaten Gianyar - Michandani, Eka Sita; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i01.p17, 2019)
This research was made to build a design of destination branding for Tourist Village Kerta in Payangan Districts, Gianyar Regency. The Method that being used is qualitative description. The informant determination technique that being used are purposive sampling technique. The data sources that being used are secondary data sources and primary data sources. The Primary data on this report is a data that comes from the observation, focus group discussion (FGD) and interview. While the secondary data on this report comes from the documentation and literature study to completed the primary data. The result from this research showing us that a brand from Tourist Village Kerta is a Climatic Village. Climatic Village was choosen as Tourist Village Kerta brand because Kerta Village has won many awards as Climatic Village. The logo design of Kerta Village as Climatic Village is described with four components such as a bamboo, a cow or a cattle, human and a temple. The bamboo, cattle and human was connected to the Tri Hita Karana concept, while the temple showing us the connection between human and the God. Keywords: Destination Branding, Tourist Village Kerta, Climatic Village